Classical Triad and Periventricular Lesions Do Not Necessarily Indicate Wernicke's Encephalopathy: A Case Report and Review of the Literature - Ye, Lisha; Xu, Zhouwei; Deng, Jiangshan; Yang, Jiajun (Frontiers in Neurology, 2020)
The classical triad—ophthalmoplegia, cerebellar dysfunction and altered mental state, in addition to bilateral symmetrical periventricular lesions are actually common to see, and clinicians tend to associate that with Wernicke’s encephalopathy (WE). The diagnosis will be strengthened with a likely deficiency of thiamine. We herein describe a malnourished patient with clinical triad and hyperintensities in the circumventricular regions, while she turned out to be a Neuromyelitis optica spectrum disorder (NMOSD) after many twists and turns. Despite totally different pathogenic mechanisms, NMOSD can mimic WE, sometimes even exhibit radiological features similar to that of WE, thereby complicating the diagnosis. Our case highlights how similar these two diseases could be and the importance of differential diagnosis in clinical practice, which are so far rarely reported. Some clinical and radiological differences of these two diseases are summarized to help establish a prompt diagnosis.